Prediksi Cuaca Kota Denpasar menggunakan Algoritma ELM dengan Optimasi Quantum Delta Particle Swarm Optimization - Adam Sulthoni Akbar; Candra Dewi; Randy Cahya Wihandika (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Weather is an important factor for beach visitors on the island of Bali, especially in the city of Denpasar. Clear weather, is the perfect weather to visit the beach. To make tourist not come to beach when weather it's rainy, a weather prediction is needed, so tourists can determine the right time to visit the beach in the city of Denpasar. Weather is a natural phenomenon that occurs in a relatively short period of time. Weather data is collected via satellite, and can be used to predict the weather in the future. In this research, the weather data used were temperature, wind speed, humidity and air pressure. To make these predictions, an artificial neural network using the Extreme Machine Learning method is used, with the optimization of the Quantum Delta Particle Swarm Optimization. With 5 hidden neuron, the result of accuracy from ELM is 39%, otherwise, with QDPSO optimization with 10 particles, 42 iterations, and g value 0,96, have result 100% accuracy.